Enhancing the Undergraduate Research Experience by Engaging in Cross-Institutional Research. Issue 1 (2nd January 2023) - Donovan, Elizabeth A.; Wiglesworth, Lesley W.
Abstract : As studies repeatedly show the benefits of students participating in undergraduate research, off-campus research opportunities have become increasingly competitive. In order to provide our students with research experiences, students from Murray State University and Centre College engaged in a year-long cross-institutional undergraduate research experience. In this paper, we summarize our experience and provide some useful perspectives in mentoring students in cross-institutional undergraduate research. We present effective methods for improving distance collaboration and strategies for eliciting the best research from students.